Enterococcus faecalis: pathogen of relevance in endodontic treatment failures - Reyes Salazar, Nicole Nohelia (2021)
Enterococcus faecalis is a microorganism related to different disease including endodontic infections. Due to its presence in the root canals after completing an endodontic treatment, its is related to the faulures of these tratments. This bacterium has variety of virulence factors such as hemolysin, gelatinase and its ability to resist multiple antimicrobials make it an extremely aggressive microorganism. It is a pathogen present in bacteremia and systemic disease. This review will allow to know a litle more about this micoorganism trying to focus on the infectious processes of the root canals.